Correlation of effectiveness and tolerability assessments from a pharmacy-based observational study investigating the fixed-dose combination of 400 mg ibuprofen plus 100 mg caffeine for the treatment of acute headache - Gaul, Charly; Förderreuther, Stefanie; Lehmacher, Walter; Weiser, Thomas (Frontiers in Neurology, 2023)
Introduction Observational studies are valuable for investigating correlations between patient-reported treatment outcomes. In this study, we report a secondary analysis of a published pharmacy-based observational (patient-centered “real-world” outcomes) study on experiences reported by patients who treated their headache with an over-the-counter analgesic. Methods A pharmacy-based exploratory survey was conducted in German community pharmacies. Patients buying a fixed-dose analgesic combination product (400 mg ibuprofen + 100 mg caffeine; IbuCaff) to treat their headache were offered a questionnaire that contained—among others—questions about time to onset of pain relief (OPR), assessment of time to onset of pain relief (AOPR), assessment of efficacy and tolerability, and pain intensity 2 h after intake. A correlation analysis of the data was performed. Moreover, perceived treatment effects compared to other acute headache medications used in the past were collected. Results The correlation between OPR and AOPR was high (Spearman rank correlation r = 0.594, p < 0.0001). Headache patients assessed the onset of analgesic action within 15 min as “very fast” and within 30 min as “fast”. The other readouts were correlated as well [assessment of efficacy and % pain intensity difference (%PID) at 2 h: r = 0.487; OPR/AOPR and %PID at 2 h: r = 0.295/0.318; OPR/AOPR and assessment of tolerability: r = 0.206/0.397; OPR/AOPR and assessment of efficacy: r = 0.406/0.594; assessment of efficacy and assessment of tolerability: r = 0.608; p < 0.0001 for all correlations]. Compared to previous treatments, most patients (>89%) assessed the speed of analgesic action, efficacy, and tolerability of IbuCaff as equal to or better than for the previous treatment. Discussion Headache patients assessed the onset of analgesia within 15 min as “very fast” and within 30 min as “fast”. Efficacy assessments for acute headache medication appear to be highly correlated.